2014
DOI: 10.1021/op5003165
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of ReactIR in Fit for Purpose Process Enablement

Abstract: An efficient four-step synthesis of 1 is described in which utilization of ReactIR was key to efficient processing and reaction monitoring. Key chemical steps included (i) nucleophilic aromatic substitution, iron reduction of aromatic nitro group to aniline, (ii) decarboxylation, and (iii) ester formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…A combination of 6 Li, 15 N, and 19 F NMR spectroscopies ,, and in situ IR spectroscopy were used to determine the solvation and aggregation states of observable intermediates and monitor reaction rates. Isotopic labeling shows whether a proton transfer is rate limiting but, as our results demonstrate, offers far more than that.…”
Section: Methods and Strategiesmentioning
confidence: 99%
“…A combination of 6 Li, 15 N, and 19 F NMR spectroscopies ,, and in situ IR spectroscopy were used to determine the solvation and aggregation states of observable intermediates and monitor reaction rates. Isotopic labeling shows whether a proton transfer is rate limiting but, as our results demonstrate, offers far more than that.…”
Section: Methods and Strategiesmentioning
confidence: 99%
“…Activation of the Ant amide bond fragmentations in the presence of strong acid, suggesting that these reactions proceed via an acid-promoted activation of the amide followed by an intramolecular cyclization mechanism. [80][81][82] Fortunately, we found that if the next amino acid was coupled (Thr), then only small amounts of the benzoxazinone fragment was detected. Upon analyzing this elongated peptide (where the Thr has been attached) by HPLC-MS, we determined that the reaction of peptide 2.44 and 2.22 using triphosgene/2,4,6-collidine was sluggish and required 19 h to be completely converted into peptide 2.45.…”
Section: The Synthesis Of Sclerotide Amentioning
confidence: 85%
“…Enolizations of 9 with recrystallized LiHMDS 15 in THF–hydrocarbon mixtures were monitored using in situ IR spectroscopy 16 to follow the loss of the oxazolidinone absorbance at 1783–1793 cm −1 and appearance of an enolate absorbance at 1733–1740 cm −1 17 . We found no evidence of precomplexation except at very low THF concentrations, 18 conditions that were assiduously avoided.…”
Section: Resultsmentioning
confidence: 99%